Catalytic Conversion of Cellulose to 5-hydroxymethylfurfural (5-HMF) Over Nano SO42--ZrO2 /MCM-41 Catalysts - Tung Son, Pham; Ha Giang, Le; Ba Manh, Nguyen; Thu Trang, Pham Thi; Quang Loi, Vu; Thanh Son, Le; Anh Tuan, Vu (VNU Journal of Science: Natural Sciences and Technology, 2020)
A zirconium catalyst system supported on MCM-41 (S-Z) with various weight components (4-20 wt.%) Was synthesized by the sol-gel method. Structure and Morphology Catalysts were characterized by X-RD, TEM, BET, FT-IR and TPD-NH 3 methods. In this catalyst, ZrO 2 is highly dispersed on the surface of MCM-41 capillaries. Catalytic activity and selectivity were evaluated by the effectiveness of mild hydrothermal decomposition of cellulose to 5-hydroxymethyl furfural (5-HMF). The results show that a catalyst with medium acidity exhibits a high selectivity of 5-HMF. Keywords: S-Zr/MCM-41 materials, sol-gel methods, cellulose, 5-HMF.